Spike Lee's Do the right thing - 4 0 16; (Mark A.) Reid, Mark; 5 (Cambridge, UK ;;New York : Cambridge University Press, 1997)
Presents five essays that examine the themes of Spike Lee's 1989 film Do the Right Thing, as well as its production history, music, and New York's urban sociology in the 1980s.
Includes bibliographical references (p. 153-155), filmography (p. 129-133), and index.
Adult;Adult
Keywords: Lee, Spike.;Lee, Spike. -- 0; 6; Do the right thing (Motion picture);Do the right thing (Motion picture); 20; 20; 2